Tingkat Pengetahuan Siswa Kelas X SMK Tunas Bangsa Terhadap Kesiapsiagaan Bencana Gempabumi Di Kabupaten Sukoharjo - Mugi Rahayu, Wahyu (2016)
Sukoharjo is one of the districts in Central Java and an area prone to natural disasters one earthquake disaster. On May 27, 2006 Sukoharjo hit by earthquakes. Agency Survey US Geological Survey (U.S. Geological Survey) recorded the quake at 6.3 on the Richter scale at a depth of 10 km, with the epicenter located on the mainland south of Yogyakarta on 7o96'2 "South Latitude, 110o45'8" East Longitude. Research This is done in vocational SMK TUNAS BANGSA which aims to determine: (1) the level of knowledge of students of class X of the earthquake disaster, (2) the level of preparedness class X in the earthquake disaster. Sample of this research is Students of class X SMK TUNAS BANGSA totaling 153 students from the amount population 355. The sample totaled 153 students. The sampling technique used was a systematic sampling. Data collection technique used Likert scale questionnaire and Guttman scale questionnaire, observation and documentation. Test requirements analysis was performed to test the validity and reliability testing. Result research shows that the level of knowledge about the class X earthquake disaster included in the category of very tau. It is based the results of data analysis showed that the percentage of the level of knowledge class X of the earthquake disaster which also covers earthquakes 59.47%, and the characteristics of the phenomenon of earthquakes 54.24%, 45.09% causes earthquakes, 7.84% strength earthquake. The level of preparedness of students of class X on disasters earthquake included in the category is not ready. It is based on the results Data analysis showed that the percentage of the level of knowledge of students of class X in earthquake preparedness is 33.24619%